Dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene photoresistor: Generation of photocarriers and charge trapping - Fernandes, José Diego [UNESP]; Vieira, Douglas Henrique [UNESP]; Klem, Maykel dos Santos [UNESP]; Alves, Neri [UNESP] (Elsevier, 2023)
Thin films of organic semiconductors have been used as active layer in several electronic devices. The molecular organization of the active layer can be a critical parameter to optimize the performance of these devices. In this work, a thin film photoresistor of Dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene (DNTT) was fabricated using physical vapor deposition (PVD) technique with the most appropriate molecular organization to obtain better performance. The DNTT photoresistor current exhibited a significant increase under ultraviolet (UV) light (λ = 390 nm, Pd = 1.73 W/m2), achieving an IUV/IDark ratio of 1 × 105 at V = −1.5 V. The photoresistor DNTT achieved good values for the most important photodetector's figures of merit (FOMs), such as responsivity of 722.3 mA/W, detectivity of 1.0 × 1013 Jones and external quantum efficiency of 23000%. The measurements of real (Z′) and imaginary (Z″) impedance in the dark indicated that the electrical relaxation process is slow and of the Debye type. Nyquist plots revealed the appearance of negative capacitance (NC) at low frequencies when the photoresistor is under illumination, indicating that the photogenerated carriers can be trapped. The alternating current (AC) conductivity (σAC) measurements under lighting suggest that charge transfer occurs by hopping and those charge carriers can tunnel through the space charge region (SCR) with built-in potential generated by charges trapped. Therefore, the results showed that although the DNTT photoresistor has a good photoconductive response, its performance can be improved by reducing of traps.
Keywords: AC conductivity; DNTT photoresistor; Impedance spectroscopy; Photomultiplication; Traps